Hydrogels applied in cosmetology irradiated by ionizing radiation - ISABELLA TEREZA FERRO BARBOSA; EMÍLIA SATOSHI MIYAMARU SEO; LEONARDO GONDIM DE ANDRADE SILVA; LEILA FIGUEIREDO DE MIRANDA (Brazilian Journal of Radiation Sciences)
Hydrogels are three-dimensionally crosslinked polymers that exhibit high capacity to absorb water or solvents, without compromising its structure, allowing its application in cosmetic products, because it presents easy scattering and vehicular active principles. The use of ionizing radiation to obtain the hydrogels provides the absence of chemical initiators; sterilization; reticulation and adjustment of physical-chemical properties. In this work different types of hydrogels containing 5 wt%, 7.5 wt% and 10 wt% PVP concentrations and different radiation 25 and 20 kGy doses were prepared, maintaining 3 wt% PEG concentrations and 1 wt%, agar based on literature studies. The samples were characterized by dehydration as a function of time, acidity, visual and sensorial analyzes and stability. The results obtained showed that all the compositions are stable, have a pH close to the skin and the compositions containing 5 wt% PVP, obtained with 20 and 25 kGy radiation dose undergo greater dehydration. In sensory research, the hydrogels containing 7.5 wt% PVP, obtained with 25 kGy radiation dose, presented the best results in terms of absorption, sliding, odor, while the composition containing 10 wt% PVP obtained with 25 kGy radiation dose, proved to be inadequate in the public perception. Therefore, the hydrogels obtained with 7.5 wt% PVP, with 25 kGy radiation dose were the most suitable for applications in cosmetic products.